Introduction - Mohd Azlan, Jayasilan; Chin, Sing Yun; Wong, James Tai Hock; Lok, Lisa Choy Hong (UNIMAS Publisher and Wilmar Plantations Sdn Bhd, 2023)
The escalation of land use conversion to agriculture is one of the key drivers of the decline in critical ecosystem function and biodiversity. Vast areas of forest in the tropics have been cleared and planted for various agricultural crops including oil palm, which is one of the most important crops in many tropical countries especially Indonesia and Malaysia. The establishment of oil palm plantations is an incredibly intensive process, involving converting native vegetation, usually degraded land or logged over forest to a plantation, often leaving behind fragmented and isolated rainforest in an oil palm matrix.